Eliyahu M. Goldratt's The goal : a business graphic novel - Goldratt, Eliyahu M., 1947-2011; Zimmerman, Dwight Jon; Motter, Dean; Cox, Jeff, 1951- (Great Barrington, MA : North River Press, 2017)
Alex Rogo is a harried plant manager who has been given 90 days to save his failing factory. If he doesn't improve the plant's performance, corporate headquarters will close it down and hundreds of workers will lose their jobs. It takes a chance meeting with Jonah, a former professor, to help him break out of his conventional thinking and figure out what needs to be done. As Alex identifies the plant's problems and works with his team to find solutions, the reader gains an understanding of the fundamental concepts behind the Theory of Constraints. Visual and fun to read, The Goal: A Business Graphic Novel offers an accessible introduction to the Theory of Constraints concepts presented in The Goal, the business novel on which it was based. The Goal is widely considered to be one of the most influential business books of all time. A bestseller since it was first published in 1984, the business novel has sold over 7 million copies, been translated into 32 languages and is taught in colleges, universities, and business schools around the world. Named to Time magazine's list of the 25 Most Influential Business Management Books, it is frequently cited by executives as a favorite or must-read title.
"Based on the business novel, The Goal: a process of ongoing improvement by Eliyahu M. Goldratt and Jeff Cox"--Title page.
Keywords: Manufacturing industries -- Comic books, strips, etc; Business -- Comic books, strips, etc; Theory of constraints (Management) -- Comic books, strips, etc; Industrie manufacturiere -- Bandes dessinees.; Affaires -- Bandes dessinees.; Theorie des contraintes (Gestion) -- Bandes dessinees.; Business; Manufacturing industries; Theory of constraints (Management); Comics (Graphic works); Graphic novels; Graphic novels